EVALUATION FOR EARLY CHILDREN'S LEARNING IN THE PANDEMIC PERIOD - Siti Nindoru Rohmah; Husna Irdiana Qurotul A’yun (-, 2021)
This study aims to describe the form of evaluation of early childhood learning in a pandemic as it is today. In the world of education, it also experiences a big impact which is also very important in developing human resources. All understand that education is the main and very important foundation in human life. Early childhood education is very important, because seen from the role of early childhood education itself is to develop children's early potential and to fulfill children's growth and development in order to have readiness to attend further education. In the process of learning online early childhood education, a special strategy is needed both from the teacher and from the family in order to achieve children's success. In addition, online learning evaluations are also needed to determine children's success rates.